Establishment and Application of a High Throughput Screening System Targeting the Interaction between HCV Internal Ribosome Entry Site and Human Eukaryotic Translation Initiation Factor 3 - Zhu, Yuying; Huang, Pei; Yang, Na; Liu, Rui; Liu, Xueting; Dai, Huanqin; Zhang, Lixin; Song, Fuhang; Sun, Chaomin (Frontiers in Microbiology, 2017)
Viruses are intracellular obligate parasites, which have evolved to exploit the host cellular machinery for their replication. Human eukaryotic translation initiation factor 3 (eIF3) could be directly recruited by the HCV internal ribosome entry site (IRES) to promote the translation of viral proteins. In this study, we establish a fluorescence polarization (FP) based high throughput screening (HTS) system targeting the interaction between HCV IRES and eIF3. By screening a total of 1000 compounds with this HTS system, two compounds (Mucl39526 and NP39) are found to disturb the interaction between HCV IRES and eIF3. And these two compounds are further demonstrated to inhibit the HCV IRES-dependent translation in vitro. Thus, this HTS system is functional to screen the potential HCV replication inhibitors targeting human eIF3, which is helpful to overcome the problem of viral resistance. Surprisingly, one compound HP-3, a kind of oxytocin antagonist, is discovered to significantly enhance the interaction between HCV IRES and eIF3 by this HTS system. HP-3 is demonstrated to directly interact with HCV IRES and promote the HCV IRES-dependent translation both in vitro and in vivo, which strongly suggests that HP-3 has potentials to promote HCV replication. Therefore, this HTS system is also useful to screen the potential HCV replication enhancers, which is meaningful for understanding the viral replication and screening novel antiviral drugs. To our knowledge, this is the first HTS system targeting the interaction between eIF3 and HCV IRES, which could be applied to screen both potential HCV replication inhibitors and enhancers.